Fetal macrosomia: analysis of the maternal and neonatal outcomes and complications - Pylypenko , Natalia; Tuchkina, Iryna (The Ukrainian Scientific Medical Youth Journal, 2022)
it is well known that the health of the child depends largely on the health of his mother during pregnancy. There are no clear criteria in the available sources and clinical protocols for predicting the risk of macrosomia, which may further adversely affect pregnancy management in general. Our aim was to analyze the maternal and neonatal outcomes and complications in Ukrainian cohort of patients during pregnancy with fetal macrosomia by conducting a prospective analysis of the history of pregnancies and childbirth of adolescent girls’ mothers with gynecological pathology, born with large to gestational age from the reference indicators. This was a retrospective cohort study. 68 histories of pregnancy and childbirth were analyzed. The incidence of maternal and neonatal complications in pregnant women with macrosomia (birth weight greater than 4000 g) was compared with that in pregnancy with normal body weight (2500–4000 g). Macrosomia is associated with significantly higher maternal age and gestational age. In macrosomia, significantly more births were completed by caesarean section. With a fetal weight above 4500 g, the risk of postpartum hemorrhage increased. Macrosomia has been shown to be associated with severe adverse outcomes for both mother and fetus.